“H” sprayer effect on liquid deposition on cucumber leaves and powdery mildew prevention in the shed - Qin, Weicai; Chen, Xuan; Chen, Panyang (Frontiers in Plant Science, 2023)
To clarify the effect of droplet size on the adherence of the solution and powdery mildew control on greenhouse cucumber leaves, the effect of volume median diameter of droplets (VMD) on the deposition and maximum retention of the solution and the effect of flusilazole on the control of powdery mildew on cucumber was determined by the stem and leaf spray method. The typical fan nozzle (F110-01, F110-015, F110-02, F110-03) of the selected U.S. Teejet production VMD differs by about 90 μm. The results showed that the deposition of flusilazole solution on cucumber leaves decreased as the volume median diameter (VMD) of the droplets in-creased, and the deposition of the solution in the treatments with VMD of 120, 172 and 210 μm decreased by 22.02%, 10.37% and 46.97%, respectively, compared with the treatment with VMD of 151 μm; when the applied solution volume was 320 L/hm2, the deposition of the solution on cu-cumber leaves The highest deposition efficiency was 63.3%, and the maximum stable retention of the liquid on the leaves was about 6.6 μL/cm2. The control effect of different concentrations of flusilazole solution on cucumber powdery mildew was significantly different, and the best control effect was achieved at the dosage of 90g/hm2 of active ingredient, which was 15%-25% higher than the dosage of 50 and 70g/hm2 of active ingredient per hectare. There was also a significant differ-ence in the size of the droplet particle size on the control effect of cucumber powdery mildew at a certain concentration of the liquid. When the dosage of active ingredient was 50 and 70 g/hm2 per hectare, nozzle F110-01 had the best control effect, which was not significantly different from nozzle F110-015, but significantly different from nozzles F110-025 and F110-03. According to the results of this experiment, the use of smaller droplet spraying with a VMD of 100-150 μm for the application of diseases on the leaf parts of cucumber in the greenhouse, that is, the choice of F110-01 or F110-015 type nozzle, under the conditions of higher liquid concentration, can significantly improve the effective utilization of pharmaceuticals and disease control effect.